Constructing a relationship model of influencing factors to optimize the implementation of blended learning: an exploratory sequential design - Lin, Wang; Omar, Muhd Khaizer; Zakaria, Noor Syamilah; Zulkifli, Nurul Nadwa (Ani Publishing, 2023)
Objective: During the COVID-19 pandemic, Chinese secondary schools embraced the practice of blended learning (BL) on a large scale. Although secondary school teachers are aware of BL’s potential benefits in improving student-learning outcomes, its implementation remains challenging. Thus, the prime objective of the study analyzed the factors influencing Chinese secondary school teachers' BL implementation using an exploratory sequential design. Method: The study has employed mixed method in the qualitative phase, 13 secondary school teachers participated in the interviews. A thematic analysis was conducted to identify seven influencing factors and generate one relationship model. In the quantitative phase, the qualitative results were validated by 365 primary and secondary school teachers who participated in the 2020 Information Technology Upgrade Project 2.0 (ITU2.0). Results: The results are as follows: student ability, teaching resources, and BL curriculum positively affected workload; teaching resources positively affected student ability; teaching resources and student ability positively affected teacher-student interaction; teaching ability, student ability, and teacher-student interactive behavior directly influenced teacher motivation; teaching ability affected BL curriculum design; and teacher-student interactive behavior positively affected teaching ability. Implications: The results provide insights into the factors influencing secondary school teachers’ BL implementation; Chinese educational and school administrators can use the findings to promote BL development in secondary schools and policy formulation. Novelty: The study is among the pioneer on the issues related to Implementation of Blended Learning.